2012
DOI: 10.5688/ajpe7610195
|View full text |Cite
|
Sign up to set email alerts
|

Variety and Quantity of Professional Electives

Abstract: Objectives. To compare the elective courses offered by US colleges and schools of pharmacy to establish a benchmark for individual colleges and schools to use in assessing whether they offer a sufficient amount and variety of electives. Methods. Internet Web sites of US doctor of pharmacy (PharmD) programs were reviewed to identify the number of elective lecture-based courses and elective advanced pharmacy practice experiences (APPE) offered and required. Elective courses were grouped into categories to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A 2011 study evaluated the variety of elective courses offered in the US Schools and College of Pharmacy and found that only 14% of programmes offered an industry elective course during the didactic portion of the curriculum . Availability of an industry elective earlier in the pharmacy curriculum can help students gain deeper knowledge and expertise about pharmaceutical industry and career opportunities it offers.…”
Section: Discussionmentioning
confidence: 99%
“…A 2011 study evaluated the variety of elective courses offered in the US Schools and College of Pharmacy and found that only 14% of programmes offered an industry elective course during the didactic portion of the curriculum . Availability of an industry elective earlier in the pharmacy curriculum can help students gain deeper knowledge and expertise about pharmaceutical industry and career opportunities it offers.…”
Section: Discussionmentioning
confidence: 99%
“…As per US Accreditation Council for Pharmacy Education (ACPE) guidelines, pharmacy curricula must contain didactic elective course opportunities for students which relate to general curricular areas: biomedical sciences; pharmaceutical sciences; social, administrative, and behavioral sciences; clinical sciences; community engagement; pharmacy education; and professional practice ( ). As might be expected, based on this broad guideline US pharmacy schools collectively offer a diverse range of didactic elective courses, e.g., complementary medicine, health informatics, global health, research, and oncology [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Typically, course topic, content, and delivery method for each didactic elective course is at the discretion of the faculty member(s) teaching the course and is based on their (or their institution’s) perceived needs and goals of the students, and/or personal preference and interests [ 8 ].…”
Section: Introductionmentioning
confidence: 97%
“…19 Although LGBT health-related issues may be sparsely incorporated into various courses such as these, pharmacy programs that have a dedicated course on the topic are rare. 20,21 For example, a two-hour didactic lecture on transgender health care was included in a therapeutics course on special populations, and a panel discussion on transgender health care was incorporated into a required diversity course, which was favorably received by the students and engaged the transgender community. 20,22 Many challenges for the health care of LGBT persons exist.…”
Section: Introductionmentioning
confidence: 99%